ERASMUS IN ISTANBUL: EXPECTATIONS AND EXPERIENCES - Ergenoglu, Asli Sungur (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2017)
This paper presents an aspect of Erasmus+ Programme that lacks study on, that is the decision, the experience and the post-effects of being an Erasmus student in Istanbul in relation to the general 'Erasmus experience' throughout Europe. As the Erasmus Programme is known to enhance the relationships between European countries and create an interaction between the different parts of the continent, it is believed that the new generations would have a stronger sense of 'being European'. Grasping the idea that the identity of one not only is bound to the country of origin but also to the commonalities of the set of values, beliefs, history, culture and even the languages, the new generation is thought and expected to have a greater sense of identity, that is 'European identity'. However, Turkey can be considered as a debate area for this notion. As the Erasmus programme focuses on 'European Identity', it is a rather an ambiguous area to some, if 'Turkish identity' matches with the notion of being 'European' and the aim of the 'Erasmus Programme' is met with the agreements made with Turkey. With the aim to search this ambiguous area, a study is conducted on incoming students to Yildiz Technical University, Faculty of Architecture, between the years of 2010 and 2016. A questionnaire form consisting of questions on the 4 main topics of; Nationality and Identity, Physical environment (Architecture, landscape and cityscape), Culture and customs, Social Relations, are applied to the incoming students and the data gathered are interpreted and discussed. Additionally, the perceptions before, during and after the experience itself are sought under these main headings as to clarify the level of overlapping of the presumptions and the reality.
Keywords: Istanbul; Erasmus; European Identity; Architectural Education; STUDENT MOBILITY; Education & Educational Research